ОБЩЕТЕОРЕТИЧЕСКОЕ РЕШЕНИЕ ЗАДАЧИ НАБЛЮДЕНИЯ ВЕКТОРА ПОТОКОСЦЕПЛЕНИЯ РОТОРА АСИНХРОННОГО ДВИГАТЕЛЯ С ИСПОЛЬЗОВАНИЕМ СКОЛЬЗЯЩИХ РЕЖИМОВ - Пересада, С.М.; Трандафилов, В.Н. (Інститут електродинаміки НАН України, Київ, 2013)
An approach to the synthesis of family of sliding mode observers of induction motor rotor flux based on Lyapunov’s second method and the equivalent control method is proposed. In accordance with proposed approach the procedure of synthesis consists of two stages: on the first – forming equivalent control, which carry information about estimation errors of rotor flux vector, by the organization of sliding mode; on the second – forming required dynamics of estimation subsystem of rotor flux vector choosing corresponding matrix. An example of observer synthesis using proposed approach is demonstrated. An availability of synthesized observer is verified by mathematical simulation. References 9, figures 2.